PENGUKURAN INDEKS DAYA BELI JASA TRANSPORTASI LAUT DAN PENYEBERANGAN PADA WILAYAH TERTINGGAL - Raga, Paulus; Aksa, S. Kamran; Herdian, Tedy; Samosir, Faisal; Abigail Ponto, Karen Nevia (Jurnal Sistem Transportasi & Logistik, 2021)
Underdeveloped areas are areas inhabited by communities with various problems such as economic factors, human resources, infrastructure (infrastructure), regional capacity, accessibility, and regional characteristics. Regional development has been encouraged by various government policies, one of which is through pioneer transportation so that people, especially those in the outermost, disadvantaged, poorest, and border areas (3TP) are served and connected in order to reduce regional disparities. This study aims to measure the purchasing power index of each region / region. This study uses the Ability to Pay (ATP), Willingness to Pay (WTP), and Composite Performance Index (CPI) techniques, then formulates a formula to determine the purchasing power index of transportation services. The results of this study are to provide an index value for underdeveloped areas in Indonesia which is associated with the CPI results in regional development related to the development of sea and ferry transportation infrastructure.